Improved absorption of β-carotene by encapsulation in an oil-in-water nanoemulsion containing tea polyphenols in the aqueous phase. (February 2019) - Meng, Qilu; Long, Piaopiao; Zhou, Jie; Ho, Chi-Tang; Zou, Xiaohui; Chen, Bo; Zhang, Liang
Abstract: β-Carotene (BC) serves as an important source of provitamin A and natural edible pigment, but the application is limited because of its instability and low oral-bioavailability. A tea polyphenols-β-carotene (TP-BC) oil-in-water (O/W) nanoemulsion was prepared with the core oil phase containing BC and the water phase containing TP. During storage at three different temperatures (4, 25 and 35 °C), the TP-BC nanoemulsion had a better stability and higher retention rate of BC than BC nanoemulsion. An in vitro simulated digestion assay indicated that the BC recovery rates of TP-BC nanoemulsion at digestion phases I and II were significantly increased compared to the BC nanoemulsion. An in vivo absorption study showed that TP-BC nanoemulsion had higher conversion efficiency on vitamin A compared to the BC nanoemulsion. These results suggested that tea polyphenols are effective ingredients for improving the oral-bioavailability of BC. Graphical abstract: Unlabelled Image Highlights: Tea polyphenols β-carotene nanoemulsion were prepared by high pressure homogenization. Tea polyphenols improved the nano-properties of β-carotene nanoemulsion during storage. The retention rate of β-carotene in nanoemulsion was increased by tea polyphenols. The vitamin A levels of rat liver after nanoemulsion intake was increased by tea polyphenols.